The fecal microbiome of dogs with exocrine pancreatic insufficiency. (June 2017) - Isaiah, Anitha; Parambeth, Joseph Cyrus; Steiner, Jörg M.; Lidbury, Jonathan A.; Suchodolski, Jan S.
Abstract: Exocrine pancreatic insufficiency (EPI) in dogs is a syndrome of inadequate synthesis and secretion of pancreatic enzymes. Small intestinal bacterial dysbiosis occurs in dogs with EPI, and is reversed with pancreatic enzyme therapy. However, there are no studies evaluating the fecal microbiome of dogs with EPI. The objective of this study was to evaluate the fecal microbiome of dogs with EPI. Three day pooled fecal samples were collected from healthy dogs (n = 18), untreated (n = 7) dogs with EPI, and dogs with EPI treated with enzyme replacement therapy (n = 19). Extracted DNA from fecal samples was used for Illumina sequencing of the bacterial 16S rRNA gene and analyzed using Quantitative Insights Into Microbial Ecology (QIIME) and PICRUSt was used to predict the functional gene content of the microbiome. Linear discriminant analysis effect size (LEfSe) revealed significant differences in bacterial groups and functional genes between the healthy dogs and dogs with EPI. There was a significant difference in fecal microbial communities when healthy dogs were compared to treated and untreated dogs with EPI (unweighted UniFrac distance, ANOSIM P = 0.001, and 0.001 respectively). Alpha diversity was significantly decreased in untreated and treated EPI dogs when compared to the healthy dogs with respect to Chao1, Observed OTU, and Shannon diversity ( P = 0.008, 0.003, and 0.002 respectively). The families Bifidobacteriaceae ( P = 0.005), Enterococcaceae ( P = 0.018), and Lactobacillaceae ( P = 0.001) were significantly increased in the untreated and treated dogs with EPI when compared to healthy dogs. In contrast, Lachnospiraceae ( P < 0.001), and Ruminococcaceae ( P < 0.01) were significantly decreased in dogs with EPI. Dogs with EPI (before treatment) had significant increases in functional genes associated with secretion system, fatty acid metabolism, and phosphotransferase system. In contrast, healthy dogs had a significant increase in genes related to phenylalanine, tyrosine and tryptophan biosynthesis, transcription machinery and sporulation. In conclusion, this study shows that the fecal microbiome of dogs with EPI (both treated and untreated) is different to that of healthy dogs.